PENGARUH METODE PEER EDUCATION DALAM MENINGKATKAN PERILAKU PERSONAL HYGIENE GENETALIA PADA REMAJA PUTRI DI DESA PUNGKA - Katrina Novita Dairo; Yunita Lestari; Luh Putu Sri Yuliastuti (Jurnal Kesehatan dan Sains, 2021)
Peer education is a process of communication, information,  and education (KIE) conducted by peers and for the peers themselves. The purpose of this study is the known influence of Peer Education Method in Improving Genetalia Personal Hygiene Behavior in Young Women in Pungka Village. The type and design of the research is quasi experiment using pretest-posttest with control group design. This research was conducted in June 2021. The population in this study was young women in Pungka village with a sample of 50  respondents divided into two groups. Analysis of the data used is univariate and ancova to determine the influence of interventions. The results showed there is a meaningful average difference in knowledge variables with a value of p = 0.003; α < 0.05 which means that there is an influence of peer education in improving the behavior of personal hygiene genetalia young women in Pungka Village by controlling the influence of pretest covariate. From the results of the study, it can be concluded that there is an influence of peer education in improving the behavior of personal hygiene genetalia young women in Pungka Village.